Process for industrially preparing nanometer aluminum oxide
By adding high-purity alumina seeds in the preparation process of nano-alumina and using ammonium salt dispersant to coordinate dispersion with vitamin C, the problems of high calcining temperature and uneven particle size in the prior art are solved, and high purity and fine particle size are achieved nanoalumina preparation.
Patent Information
- Application Number
- CN202411655643.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, when nano-alumina is prepared, the calcination temperature is high, the particle size is uneven, and the dispersion is poor, resulting in unsatisfactory purity and particle size distribution of the product.
By adding high-purity alumina seeds, using high-purity aluminum chloride and high-purity ammonium carbonate as raw materials, combining ammonium salt dispersant and vitamin C to disperse together, reducing the calcination temperature and controlling the particle size distribution.
The high purity, fine particle size and uniform distribution of nano-alumina are achieved, which reduces the calcination temperature and improves the preparation efficiency.
Smart Images

Figure CN119461433A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano material preparation, and in particular relates to a process for industrially preparing nano aluminum oxide. Background Art
[0002] There are many types of alumina, including up to 12 types including amorphous alumina. The most common ones are α-Al2O3, β-Al2O3 and γ-Al2O3. Nano-scale α-Al2O has a series of excellent properties such as high strength, heat resistance, high hardness, wear resistance, chemical corrosion resistance, etc., and has a very broad application space in the fields of refractory materials, fine ceramics, coatings, etc.; while nano-scale γ-Al2O3 is widely used in biomedicine, catalysis, composite materials and other fields due to its high porosity, good adsorption capacity and large specific surface area. The liquid phase method for preparing nano-alumina has mild conditions and a relatively simple process. As researchers continue to improve the preparation method and process, the liquid phase method has gradually become the focus of research and application.
[0003] Liquid phase methods can be divided into precipitation method, hydrothermal synthesis method, sol-gel method, microemulsion method and electrochemical method. Compared with other methods, precipitation method has attracted attention due to its simple equipment, easy availability of raw materials, high product purity, and easy to effectively control the structure, morphology and particle size of the product by changing the reaction conditions (such as reaction temperature, reactant concentration and solution pH value, etc.), and has become the most commonly used method for industrial preparation of nano-alumina particles. When preparing nano-alumina, it is often necessary to add high-purity alumina as a seed to reduce the nucleation barrier and nucleation work and reduce the calcination temperature. The alumina obtained by aluminum alkoxide hydrolysis and roasting method has a high purity and is one of the methods for preparing high-purity alumina. However, in the current preparation method, the precursor needs to be calcined at a higher temperature to obtain α-Al2O3, and the alumina is easy to agglomerate, which limits the particle size of the alumina. Moreover, in the prior art, due to different reaction conditions, the prepared alumina has problems such as irregular particle morphology, poor dispersibility, and uneven particle size distribution. Summary of the invention
[0004] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides a process for industrially preparing nano-alumina, by adding high-purity alumina seeds to reduce the calcination temperature of α-Al2O3; the high-purity alumina seeds are made of high-purity aluminum chloride and high-purity ammonium carbonate as raw materials, and are synergistically dispersed with an ammonium salt dispersant and high-purity vitamin C, and calcined to obtain the obtained high-purity alumina seeds and the nano-alumina prepared therefrom, which have high purity, small and uniform powder particle size.
[0005] The technical solution to achieve the purpose of the present invention is as follows: a process for industrial preparation of nano-alumina, the process comprising:
[0006] S1. Use a mixed solution of water and ethanol as a solvent to prepare equal volumes of aluminum salt solution and precipitant solution, add high-purity alumina seeds and dispersant to the precipitant solution, stir evenly, pour the aluminum salt solution into the precipitant solution at one time, react for 30 to 60 minutes, filter, wash the obtained precipitate with a mixed solvent of water and ethanol at least twice, and dry to obtain a precursor;
[0007] S2. The precursor is calcined, kept warm, and cooled with the furnace to obtain nano-alumina;
[0008] The method for preparing the high-purity alumina seed crystal is as follows:
[0009] Using a mixed solution of ultrapure water and ethanol as a solvent to prepare equal volumes of high-purity aluminum chloride solution and high-purity ammonium carbonate solution, adding an ammonium salt dispersant and vitamin C to the high-purity ammonium carbonate solution, stirring evenly, pouring the high-purity aluminum chloride solution into the high-purity ammonium carbonate solution at once under ultrasonic conditions, reacting for 20 to 30 minutes, and then filtering to obtain an ultrapure precursor, which is directly calcined without washing, kept warm, and cooled with the furnace to obtain high-purity alumina seed crystals;
[0010] The ammonium salt dispersant has at least one of the following structures:
[0011]
[0012] In Formula I and Formula II, X=F, Cl, Br; n=8~230.
[0013] Preferably, the ammonium salt dispersant has the following structure:
[0014] In formula I, X=F; n=8-50.
[0015] Due to the strong electronegativity of fluoride ions, the rearrangement of Al and O atoms will be accelerated at 900-950°C, prompting the reconstruction phase transition of Al2O3, thereby reducing the temperature required to complete the α phase transition.
[0016] Specifically, the preparation method of X=F in the structure of Formula I is as follows:
[0017] (1) In a nitrogen atmosphere and an ice bath, polyethylene glycol and pyridine are dissolved in a 1,4-dioxane solvent in a reaction kettle, and dichlorothionyl is slowly added dropwise to the reaction kettle. After the addition is completed, the temperature is raised to 75-85° C., and the reaction is continued for 5-24 hours. After cooling to room temperature, the solvent is removed by rotary evaporation, and the product is dissolved in a dichloromethane solvent, and washed at least twice with a dilute hydrochloric acid solution. The organic layer is collected, dried over anhydrous magnesium sulfate, and then dried by rotary evaporation to obtain a double-terminated polyethylene glycol;
[0018] (2) dispersing triethylamine and the double-terminated polyethylene glycol obtained in step (1) in acetonitrile, stirring at 50-80° C. for 8-10 hours, cooling to room temperature, washing with a dilute hydrochloric acid solution at least twice, collecting the organic layer, drying over anhydrous magnesium sulfate, and spin-drying to obtain quaternized polyethylene glycol;
[0019] (3) The quaternized polyethylene glycol and potassium fluoride obtained in step (2) are dispersed in methanol and stirred at room temperature for 30 to 60 minutes to obtain an ammonium salt dispersant with X=F.
[0020] Preferably, the volume ratio of the mixed solution of water and ethanol is 1:1-3:1; the volume ratio of the mixed solution of ultrapure water and ethanol is (1-3):1; the molar ratio of the aluminum salt and the precipitant is 1:(8-10); and the molar ratio of the high-purity aluminum chloride and high-purity ammonium carbonate is 1:(8-10).
[0021] Preferably, the high-purity alumina seeds are 2.0-3.0wt.% of the precipitant solution; the dispersant is 5.0-7.0wt.% of the precipitant solution; the ammonium salt dispersant is 4.0-6.0wt.% of the high-purity ammonium carbonate solution; and the high-purity vitamin C is 0.5-1.0wt.% of the high-purity ammonium carbonate solution.
[0022] Preferably, the drying temperature is 80-90°C, and the drying time is 60-90 min; the precursor calcination temperature is 400-1300°C, the heating rate is 5-10°C / min, and the calcination time is 2-4 h; the ultrapure precursor calcination temperature is 400-1300°C, the heating rate is 5-10°C / min, and the calcination time is 2-4 h.
[0023] Preferably, the aluminum salt is one or more of aluminum sulfate, aluminum chloride and aluminum nitrate; the precipitant is one or more of ammonium carbonate, sodium carbonate, ammonium bicarbonate and sodium bicarbonate; the dispersant is one or more of polyethylene glycol, polyvinyl alcohol, vitamin C and citric acid.
[0024] More preferably, the aluminum salt is aluminum sulfate; the precipitant is ammonium bicarbonate; and the dispersant is at least one of polyethylene glycol and vitamin C.
[0025] More preferably, the average molecular weight of the polyethylene glycol is 2000.
[0026] Preferably, the purity of the high-purity aluminum chloride and high-purity vitamin C is 99.99%; the purity of the high-purity ammonium carbonate is 99.999%.
[0027] Beneficial Effects
[0028] The present invention has the following beneficial effects: the nano-alumina prepared by the present invention has the advantages of small powder particle size and high particle size uniformity;
[0029] 1) When the precipitation method used in the present invention is used to prepare the nano-alumina precursor, there is no need to add the aluminum salt solution drop by drop, and it can be directly poured in and quickly mixed, and there is no sedimentation step, which reduces the preparation time.
[0030] 2) High-purity alumina seeds were introduced into the precursor, which reduced the calcination temperature of α-Al2O3.
[0031] 3) When preparing high-purity alumina seeds, ammonium salt dispersants and vitamin C are used to coordinately control the components, wherein the ammonium salt dispersant is double-terminated tetraethylammonium fluoride polyethylene glycol, which synergistically disperses the precursor through steric hindrance and charge repulsion, and provides fluoride ions during calcination, thereby reducing the temperature required to complete the α phase transition; vitamin C can be embedded in the gaps between the ammonium salt dispersant macromolecules, and has a certain effect on regulating the particle size; all reagents used are high-purity reagents, and all dispersants used can be completely removed at high temperature without washing. When decomposed at high temperature, the NH3, H2O, and CO2 gases produced can effectively reduce the agglomeration of particles, which is beneficial to the refinement of the grain size. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 X-ray diffraction patterns of high-purity alumina seed crystals 1 and 4 prepared in the present invention;
[0033] Figure 2 X-ray diffraction patterns of Example 1 and Comparative Example 1 prepared in the present invention;
[0034] Figure 3 This is a transmission electron microscope photograph of Example 1 prepared in the present invention.
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0037] The raw materials and equipment used in the embodiments and comparative examples are described as follows:
[0038] Ammonium bicarbonate: purity 99.0%, product number 1214683, purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd.;
[0039] Aluminum sulfate: purity 99.0%, purchased from Nantong Runfeng Petrochemical Co., Ltd.;
[0040] Polyethylene glycol 1: average molecular weight 400, product number A55792, purchased from Beijing Wokai Biotechnology;
[0041] Polyethylene glycol 2: average molecular weight 1000, product number A55795, purchased from Beijing Wokai Biotechnology;
[0042] Polyethylene glycol 3: average molecular weight 2000, product number A55797, purchased from Beijing Wokai Biotechnology;
[0043] Vitamin C: purity 98.0%, product number YB33843, purchased from Hunan Yunbang Biology;
[0044] High-purity vitamin C: purity 99.99%, product number A55795, purchased from Beijing Wokai Biological;
[0045] High-purity aluminum chloride: purity 99.99%, product number A433483, purchased from Shanghai Aladdin Biochemical;
[0046] High-purity ammonium carbonate: purity 99.999%, product number A800847, purchased from Shanghai McLean Biochemical;
[0047] Thionyl chloride: Product No. T110473, purchased from Shanghai Aladdin Biochemical;
[0048] Potassium fluoride: Product No. P164507, purchased from Shanghai Aladdin Biochemical.
[0049] Ultrapure water (homemade): MILLIPORE DirectQ3UV, MILLIPORE, France;
[0050] Ammonium salt dispersant 1 (self-made)
[0051] (1) In a nitrogen atmosphere and an ice bath, 1 mol of polyethylene glycol 1 and 3 mol of pyridine are dissolved in 1,4-dioxane solvent in a reaction kettle, and 2.6 mol of dichlorothionyl is slowly added dropwise to the reaction kettle. After the addition is completed, the temperature is raised to 80° C., and the reaction is continued for 18 hours. After cooling to room temperature, the solvent is removed by rotary evaporation, and the product is dissolved in dichloromethane solvent, and washed three times with 1-2 mol / L hydrochloric acid dilute solution. The organic layer is collected, dried over anhydrous magnesium sulfate, and dried by rotary evaporation to obtain double-terminated polyethylene glycol;
[0052] (2) dispersing 8 mol of triethylamine and 1 mol of the double-terminated polyethylene glycol obtained in step (1) in acetonitrile, stirring at 80° C. for 10 h, cooling to room temperature, and removing the solvent by rotary evaporation. The product is dissolved in dichloromethane solvent, washed three times with 1-2 mol / L hydrochloric acid dilute solution, collecting the organic layer, drying over anhydrous magnesium sulfate, and rotary drying to obtain quaternized polyethylene glycol;
[0053] (3) 1 mol of quaternized polyethylene glycol obtained in step (2) and 10 mol of potassium fluoride are dispersed in methanol, stirred at room temperature for 60 min, filtered to remove solids, and the obtained product is dissolved in dichloromethane, washed with deionized water three times, and the solvent is removed to obtain the product ammonium salt dispersant 1.
[0054] Ammonium salt dispersant 2
[0055] The preparation method is compared with the ammonium salt dispersant 1, and the difference lies in that polyethylene glycol 1 is replaced by polyethylene glycol 2.
[0056] Ammonium salt dispersant 3
[0057] The preparation method is different from that of ammonium salt dispersant 1, in that polyethylene glycol 1 is replaced by polyethylene glycol 3.
[0058] The high purity alumina seed crystal 1 is prepared as follows:
[0059] A mixed solution of 50 mL of ultrapure water and 50 mL of ethanol was used as a solvent to prepare equal volumes of high-purity aluminum chloride solution (0.2 mol / L) and high-purity ammonium carbonate solution (0.9 mol / L). 4 g of ammonium salt dispersant 1 and 1 g of high-purity vitamin C were added to the high-purity ammonium carbonate solution. After stirring evenly, the high-purity aluminum chloride solution was poured into the high-purity ammonium carbonate solution under ultrasonic conditions at one time and reacted for 30 minutes. The precursor was then filtered to obtain an ultrapure precursor. The precursor was calcined at 1025°C for 2 hours without washing. The temperature was increased at a rate of 10°C / min and the precursor was kept warm for 2 hours. The precursor was cooled with the furnace to obtain a high-purity alumina seed crystal 1.
[0060] High purity alumina seed 2
[0061] The preparation method is different from the high-purity alumina seed crystal 1 in that the ammonium salt dispersant 1 is replaced by the ammonium salt dispersant 2.
[0062] High purity alumina seed 3
[0063] The preparation method is different from the high-purity alumina seed crystal 1 in that the ammonium salt dispersant 1 is replaced by the ammonium salt dispersant 3.
[0064] High purity alumina seed 4
[0065] The preparation method is different from the high-purity alumina seed crystal 1 in that the ammonium salt dispersant 1 is replaced by polyethylene glycol 1.
[0066] High purity alumina seed 5
[0067] The preparation method is compared with the high-purity alumina seed crystal 1, except that 2g of high-purity vitamin C is replaced by 2g of ammonium salt dispersant 1.
[0068] The following is the test method of the performance parameters involved in the present invention:
[0069] X-ray diffraction analysis: Cu-Kα target, voltage 40kV, current 200mA, The scanning angle range is 20-70°, and the test is compared with the standard card;
[0070] Particle size distribution: laser particle size analyzer Malvern Mastersizer 2000, measuring range 0.02-2000 μm;
[0071] Morphology analysis: Transmission electron microscope, JEOL JEM-F200.
[0072] Table 1 Crystal form and particle size of high purity alumina seed crystals
[0073]
[0074] It can be seen from the data in Table 1 that with the increase of the molecular weight of the ammonium salt dispersant, the particle size distribution of the high-purity alumina seed crystals becomes narrower; when the ammonium salt dispersant is replaced by polyethylene glycol, some θ-Al2O3 crystals are not converted into α-Al2O3 after calcination at 1025°C; when high-purity vitamin C is not added, the particle size distribution of the high-purity alumina seed crystals becomes wider and the particle size becomes larger.
[0075] A process for industrial preparation of nano-alumina, the process comprising the following steps:
[0076] S1. Use a mixed solution of 50 parts of water and 50 parts of ethanol as a solvent to prepare equal volumes of aluminum sulfate solution (0.2 mol / L) and ammonium bicarbonate solution (1.6 mol / L), add 3 parts of high-purity alumina seeds and 6 parts of dispersant to the ammonium bicarbonate solution, stir evenly, pour the aluminum salt solution into the ammonium bicarbonate solution at one time and react for 60 minutes, filter, wash the resulting precipitate with a mixed solvent of water and ethanol 3 times, and dry at 90°C for 60 minutes to obtain a precursor;
[0077] S2. Calcine the precursor at 1080°C for 2 h, with a heating rate of 10°C / min and keep it at that temperature for 2 h, and cool it in the furnace to obtain nano-alumina.
[0078] Table 2 Process parameters and performance of Examples 1 to 4 and Comparative Example 1
[0079]
[0080]
[0081] It can be seen from the data in Table 2 that the addition of the high-purity alumina seeds prepared by the present invention can effectively reduce the temperature required for calcining α-Al2O3, and relatively pure nano-alumina can be obtained at 1080°C; when polyethylene glycol and vitamin C are used as mixed dispersants, the obtained particle size distribution is narrower and the particle size is smaller.
[0082] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A process for industrial preparation of nano-alumina, characterized in that: The process comprises the following steps: S1. Use a mixed solution of water and ethanol as a solvent to prepare equal volumes of aluminum salt solution and precipitant solution, add high-purity alumina seeds and dispersant to the precipitant solution, stir evenly, pour the aluminum salt solution into the precipitant solution at one time, react for 30 to 60 minutes, filter, wash the obtained precipitate with a mixed solvent of water and ethanol at least twice, and dry to obtain a precursor; S2. The precursor is calcined, kept warm, and cooled with the furnace to obtain nano-alumina; The method for preparing the high-purity alumina seed crystal is as follows: Using a mixed solution of ultrapure water and ethanol as a solvent to prepare equal volumes of high-purity aluminum chloride solution and high-purity ammonium carbonate solution, adding an ammonium salt dispersant and high-purity vitamin C into the high-purity ammonium carbonate solution, stirring evenly, pouring the high-purity aluminum chloride solution into the high-purity ammonium carbonate solution at once under ultrasonic conditions, reacting for 20 to 30 minutes, and then filtering to obtain an ultrapure precursor, which is directly calcined without washing, kept warm, and cooled with the furnace to obtain high-purity alumina seed crystals; The ammonium salt dispersant has at least one of the following structures: In Formula I and Formula II, X=F, Cl, Br; n=20~230.
2. The process for industrial preparation of nano-alumina according to claim 1, characterized in that: The volume ratio of the mixed solution of water and ethanol is (1-3):1; the volume ratio of the mixed solution of ultrapure water and ethanol is (1-3):1; the molar ratio of the aluminum salt and the precipitant is 1:(3-10); and the molar ratio of the high-purity aluminum chloride and high-purity ammonium carbonate is 1:(3-10).
3. The process for industrial preparation of nano-alumina according to claim 1, characterized in that: The high-purity alumina seed crystals account for 2.0-3.0wt.% of the precipitant solution; the dispersant accounts for 5.0-7.0wt.% of the precipitant solution; the ammonium salt dispersant accounts for 4.0-6.0wt.% of the high-purity ammonium carbonate solution; and the high-purity vitamin C accounts for 0.5-1.0wt.% of the high-purity ammonium carbonate solution.
4. The process for industrial preparation of nano-alumina according to claim 1, characterized in that: The drying temperature is 80-90°C, and the drying time is 60-90 minutes; the precursor calcination temperature is 400-1300°C, the heating rate is 5-10°C / min, and the calcination time is 2-4 hours; the ultrapure precursor calcination temperature is 400-1300°C, the heating rate is 5-10°C / min, and the calcination time is 2-4 hours.
5. The process for industrial preparation of nano-alumina according to claim 1, characterized in that: The aluminum salt is one or more of aluminum sulfate, aluminum chloride and aluminum nitrate; the precipitant is one or more of ammonium carbonate, sodium carbonate, ammonium bicarbonate and sodium bicarbonate; the dispersant is one or more of polyethylene glycol, polyvinyl alcohol, vitamin C and citric acid.
6. The process for industrial preparation of nano-alumina according to claim 1, characterized in that: The purity of the high-purity aluminum chloride and high-purity vitamin C is 99.99%; the purity of the high-purity ammonium carbonate is 99.999%.